Conformal antenna array for MIMO applications - Elwi, Taha A.; Abbas, Zulkifly; Noori, Mohammed; Al-Naiemy, Yahiea; Salih, Ethar Y.; Hamed, Marwa M. (Scientific Research Publishing, 2014)
In this paper, a numerical study is reported based on the Finite Element Method (FEM) and the Finite Integral Technique (FIT) of Ansoft’s HFSS and CST Microwave Studio (MWS) formulations, respectively, applied to a Bended Complementary Split-Ring Resonator (BCSRR) of rejection band extending from 4.1 GHz to 4.6 GHz. The proposed BCSRR structure is combined with the design of a circularly polarized cylindrical antenna array of square patches with trimmed opposite corners. The performance of the cylindrical antenna array is characterized and compared to that of the flat profile. It is found that the proposed BCSRR reduces the mutual coupling to -15 dB between two patches with a separation of only 1/11th free-space wavelength for applications involving Multi Input Multi Output (MIMO) system.